Discursive Practice and Communicative Strategy: Eclecticism vs Poly-paradigmatism? - E. A. Nikonova (Научный диалог, 2023)
The focus of this research is on the concepts of “communicative strategy” and “discursive practice,” which are frequently used today without being tied to a specific linguistic paradigm. The objective was to clarify whether these concepts can be classified as cross-paradigmatic, meaning they are not limited to a specific linguistic paradigm. The study revealed that despite their apparent similarities, these concepts differ in several key characteristics and are aimed at solving different tasks. Additionally, it was found that the main differentiation between these phenomena occurs at the level of their association with different linguistic domains: discursive practice is an element of discourse (and therefore belongs to the discursive paradigm), while communicative strategy is an element of communication (and is thus considered within the framework of the communicative-pragmatic / linguo-communicative paradigm and speech act theory). Analysis of contemporary research focused on studying communicative strategies and discursive practices showed a prevalence of a more “narrow” interpretation of the concept of “discourse,” which allows for the identification of specific forms of communicative practices within discourse. Furthermore, there is a simplification in the understanding of the implementation of discursive practices.